Case Report: Untreatable Headache in a Child With Ventriculoperitoneal Shunt Managed by Use of New Non-invasive Intracranial Pressure Waveform - Paraguassu, Geraldo; Khilnani, Mark; Rabelo, Nicollas Nunes; Cobos, Luiza D'Ottaviano; Frigieri, Gustavo (Frontiers in Neuroscience, 2021)
Brain4care, a new, FDA cleared non-invasive sensor which monitors intracranial pressure waveforms was used in a 13-year-old girl presented with untreatable headaches. The patient had a history of craniopharyngioma resection and a ventriculoperitoneal shunt placement seven years prior to the use of the device. Secondary obstructive hydrocephalus was also a present factor in the case. The hypothesis was that due to the hydrocephalus the child presented chronic headaches and needed constant readjustment into the ventriculoperitoneal shunt to regulate the cerebrospinal fluid inside her ventricles in order to control the patient’s intracranial pressure (ICP). The device was chosen considering the risks to submit a patient into the regular invasive method to measure ICP. It was identified that the device could also indicate altered intracranial compliance due to the ratio between the P1 and P2 amplitudes (P2/P1 ratio > 1).